Viral immunogenicity determines epidemiological fitness in a cohort of DENV-1 infection in Brazil - Pinheiro, Tauyne Menegaldo; Oliveira Mota, Manlio Tasso de; Aranha Watanabe, Aripuana Sakurada; Biselli-Perico, Joice Matos [UNESP]; Drumond, Betania Paiva; Ribeiro, Milene Rocha; Vedovello, Danila; Araujo, Joao Pessoa [UNESP]; Paolucci Pimenta, Paulo Filemon; Chaves, Barbara Aparecida; Carneiro da Silva, Mayara Marques; Andrade Batista, Izabella Cristina; et al. (Public Library Science, 2018)
The dynamics of dengue virus (DENV) circulation depends on serotype, genotype and lineage replacement and turnover. In Sao Jose do Rio Preto, Brazil, we observed that the L6 lineage of DENV-1 (genotype V) remained the dominant circulating lineage even after the introduction of the L1 lineage. We investigated viral fitness and immunogenicity of the L1 and L6 lineages and which factors interfered with the dynamics of DENV epidemics. The results showed a more efficient replicative fitness of L1 over L6 in mosquitoes and in human and non-human primate cell lines. Infections by the L6 lineage were associated with reduced antigenicity, weak B and T cell stimulation and weak host immune system interactions, which were associated with higher viremia. Our data, therefore, demonstrate that reduced viral immunogenicity and consequent greater viremia determined the increased epidemiological fitness of DENV-1 L6 lineage in Sao Jose do Rio Preto.